Global market of business tourism: development problems and prospects - Yuri Opanashchuk; Olena Sushchenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
An important role in the development of global international tourism is played by business tourism, or corporate tourism, aimed at meeting the needs of business travelers and forming specific trends in the development of the global tourism industry. The study of problems and prospects for the development of the global market of business tourism is aimed at the understanding by market players of its dynamics and the adoption of effective strategic solutions for its future development. The subject of research in the article is the theoretical, methodological and practical aspects of the business tourism global market development. The goal is to analyze the current state and identify trends and prospects for the business tourism global market development. The objective is to research the problems and prospects for the business tourism global market development. General scientific methods are used: systematic analysis - to determine the features of the business tourism global market development, comparative analysis - in the analysis of existing approaches to the definition of business tourism. The following results were obtained: based on the analysis of the dynamics of changes in the main indicators of the business tourism global market, the main problematic aspects and trends of its development were determined. Conclusions: business tourism is one of the most relevant industries for the tourism destination development, as it can bring significant income to the local budget. The process of business tourism development requires prior planning and preparation, including the construction or restoration of infrastructure, which requires cooperation between enterprises of different industries.